Knowledge Mobilization for Agri-Food Supply Chain Decisions: Identification of Knowledge Boundaries and Categorization of Boundary-Spanning Mechanisms - Zhao, Guoqing; Liu, Shaofeng; Elgueta Palma, Sebastián Andrés.; Manzur, Juan Pablo; López, Carmen; Chen, Huilan (IGI Global, 2022)
The current world business environment is characterized by increasing uncertainties, complexities, and risks, which require agri-food supply chain (AFSC) managers to respond and act quickly in a context full of instability and unpredictability. Increasing pressure placed on AFSC managers intensifies the need to combine knowledge management (KM) and decision support that rapidly overcome knowledge boundaries. It has been recognized that the research issue related to the knowledge mobilization crossing boundaries in the AFSC needs to be addressed. This paper investigates knowledge boundaries and boundary-spanning mechanisms by collecting data from experienced AFSC practitioners. Empirical results verify that knowledge boundaries such as syntactic boundaries, semantic boundaries, and pragmatic boundaries could be effectively tackled by four specific boundary-spanning mechanisms: boundary spanners, boundary objects, boundary practices, and boundary discourses.
Keywords: Agri-Food supply chains; Boundary-Spanning mechanisms; Knowledge boundaries; Knowledge mobilization; Toma de decisiones